2002
DOI: 10.1038/sj.bjc.6600305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of multidrug resistance-associated protein1,P-glycoprotein, and thymidylate synthase in gastric cancer patients treated with 5-fluorouracil and doxorubicin-based adjuvant chemotherapy after curative resection

Abstract: Both 5-fluorouracil and doxorubicin are commonly used agents in chemotherapy of gastric cancer in adjuvant setting as well as metastatic disease. In a variety of malignancies, high expression of multidrug resistance-associated protein1 and P-glycoprotein has been associated with resistance to doxorubicin, whereas 5-fluorouracil resistance has correlated with the level of thymidylate synthase expression. We evaluated the expression of multidrug resistance-associated protein1, P-glycoprotein, and thymidylate syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 35 publications
1
31
1
4
Order By: Relevance
“…42,43 However, several studies also failed to find an association with prognosis of specific malignancies, such as rhabdomyosarcoma 44 and Ewing sarcoma, 45 as well as types of lymphomas, 46 gastric carcinoma, 47 and mesothelioma. 48 Thus, the literature on a potential prognostic role of Pgp in sarcomas in particular has been ambivalent.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 However, several studies also failed to find an association with prognosis of specific malignancies, such as rhabdomyosarcoma 44 and Ewing sarcoma, 45 as well as types of lymphomas, 46 gastric carcinoma, 47 and mesothelioma. 48 Thus, the literature on a potential prognostic role of Pgp in sarcomas in particular has been ambivalent.…”
Section: Discussionmentioning
confidence: 99%
“…A product of the mdr1 gene, p-glycoprotein (p-gp), is a 170-kDa transmembrane protein that functions as an energy-dependent drug efflux pump, the substrates of which include a wide range of anticancer drugs. MDR1 is often overexpressed in primary gastric adenocarcinoma and its precursor lesions (Vollrath et al, 1991;Wallner et al, 1993;Lacueva et al, 1998;Choi et al, 2002). This increase in p-gp levels correlates with an increased resistance to the chemotherapeutic drug, doxorubicin, in primary gastric cancer cells (Hotta et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al (2002) found higher expression of ABCB1 protein in moderately differentiated tumors and especially in intestinal-type GC of Lauren's classification. Similarly, we found increased expression of ABCB1 protein in moderately differentiated tumors and intestinaltype of Lauren.…”
Section: Discussionmentioning
confidence: 81%